Absenteeism on bridging days - René Böheim; Thomas Leoni (Johannes Kepler University of Linz, Department of Economics, 2019)
We estimate sickness absences on Mondays and Fridays which fall between a weekend and public holidays, so called "bridging days". Many public holidays change their day of the week over the years. We find that sickness absences are considerably lower on bridging days than on regular Mondays and Fridays. Based on an investigation of diagnoses with unobservable symptoms, we do not find indications for changes in shirking behavior by workers.
Keywords: J22; 330; sickness absence; moral hazard; bridging days